Andong and Pedicab as Halal Tourism Transportation Means for Tourists in Malioboro Yogyakarta with Social Economic Approach - Andro Agil Nur Rakhmad (Maliki Islamic Economics Journal, 2021)
Tourism is one of the leading sectors that contributes significantly to Indonesia's national income. Yogyakarta is one of the regions in Indonesia that can run halal tourism. because yogyakarta is one of the provinces that has many tourist attractions. In addition, the majority of the population of Yogyakarta is Muslim. Therefore, it has potential in the development of halal tourism. One of the things that attracts the attention of both local and international tourists is the traditional vehicles in this city. The traditional vehicles are andong and pedicap. This research is descriptive qualitative by using an inductive approach. The theoretical basis is used as a guide so that the research focus is in accordance with the facts on the ground. In this study, we as researchers started from the data, using the existing theory as explanatory material. Andong adn pedicab being a passenger transport. The uniqueness and peculiarity of the andong and pedicab make it not only an ordinary transportation but has become part of a halal tourist attraction that is quite popular with tourists in the Malioboro area.